Transparent metasurface for wideband backward scattering reduction with synthetic optimization algorithm. (7th July 2022) - Sui, Sai; Wang, Jiafu; Pang, Yongqiang; Zhang, Jieqiu; Xu, Zhuo; Qu, Shaobo
Abstract: An optical transparent metasurface for wideband backward scattering reduction with a synthetic optimization method is proposed, which makes full use of the simultaneity of electromagnetic absorption and interference suppression, so that backward scattering can be flexibly manipulated. To validate the design procedure, a metasurface with optical transparency is designed, fabricated and experimentally tested, which significantly enhances the efficiency in the frequency range of 6.2–20.8 GHz and exhibits about 79.5% averaged transmittance of optical transparency in the wavelength range of 380–780 nm. The proposed optical transparent wideband backward scattering reduction metasurface reveals an alternative opportunity for effective manipulation of microwaves.